Kuthomoro tradition: Using its potential ethnobotany for biology learning resources - Moro, Hendro Kusumo Eko Prasetyo; Handayani, Nida Dwi; Fitria, Ayu (International Journal on Education Insight, 2025)
Ethnobotany is the study of plants from the point of view of local residents who still hold traditions from generation to generation. Kuthomoro tradition is a praying tradition to the ancestor by Karaton Yogyakarta, one of the kingdoms in Indonesia that still stands until today. The tradition largely uses plants as the ritual equipment, however, the research about the use of Kuthomoro context as a learning resource for senior high school biology learning is still limited. This study aims to determine the types of plants and the symbolic meanings used in the Kuthomoro tradition in the ancient tomb of Giriloyo and Imogiri. This study also identified the potential resources of biology learning for 10th-grade senior high school. It was a qualitative research, involving 6 respondents from juru kunci (the key keeper) and abdi dalem (Kingdom’s employee) of Giriloyo and Imogiri tomb. The objects of this research are flowers and traditional dishes called ubarampe usually used for offering in Kuthomoro tradition. We used observation, in-depth interview, and documentation to collect the data, and used descriptive technique for the data analysis referring to Djohar’s criteria to study the potential biology learning sources. The results showed that there were 44 types of plants used in Giriloyo and 50 types of plants used in Imogiri for the ubarampe offering purposes. The symbolic meaning of the plants used in this tradition is a prayer and wishes that the ancestors’ sin would be forgiven and get a better condition in the afterlife. The various types of plants used in both tombs can be used as a resource for senior high school biology learning.